2012
DOI: 10.1111/j.1469-7610.2012.02560.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation in the context of frustration in children with high functioning autism and their typical peers

Abstract: The results go beyond the recent literature by offering a rich description of children's efforts to regulate their frustration when faced with challenge, and point to important contextual differences in the efficacy of children's coping strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
125
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(141 citation statements)
references
References 37 publications
15
125
0
1
Order By: Relevance
“…Indeed, our results are consistent with recent studies in which the social and emotional development of children with ASD appears different when analyzed within the context of interactions with primary caregivers (Hirschler-Guttenberg et al 2015;Jahromi et al 2012;Warreyn et al 2005). For example, during the observation of spontaneous play, mothers of children with and without ASD were asked to respond briefly to their children's demands and also asked to restrict further interactions (Warreyn et al 2005).…”
Section: Dyadic Flexibility Of Mother-child Interactionssupporting
confidence: 80%
See 1 more Smart Citation
“…Indeed, our results are consistent with recent studies in which the social and emotional development of children with ASD appears different when analyzed within the context of interactions with primary caregivers (Hirschler-Guttenberg et al 2015;Jahromi et al 2012;Warreyn et al 2005). For example, during the observation of spontaneous play, mothers of children with and without ASD were asked to respond briefly to their children's demands and also asked to restrict further interactions (Warreyn et al 2005).…”
Section: Dyadic Flexibility Of Mother-child Interactionssupporting
confidence: 80%
“…Children with ASD tend be less accurate with their identification of emotions and recognition of facial expressions across the six basic emotions (e.g., happiness, anger) (Lozier et al 2014). Two studies demonstrated that, compared to TD children, children with ASD tended to use more avoidance and venting strategies and employed less attention shifting and inhibitory control strategies in a frustration-eliciting stimulus (Konstantareas and Stewart 2006;Jahromi et al 2012). However, in a study where mothers and children were observed across three interaction contexts (free-play, a structured communication context, and a face-to-face interaction), young children with ASD did not differ from TD children in frequency or duration of smiles and frowns, although they showed fewer smiles in direct response to their mothers' smile (Dawson et al 1990).…”
mentioning
confidence: 99%
“…Six of the 10 studies that included naturalistic observation/behavior coding did so for more than one behavior. For example, Jahromi et al [2012] included naturalistic observation/behavioral codes for four separate behavioral indicators (i.e. negative and nonnegative vocalizations, resignation behaviors, facial affect and bodily negativity, and ER coping strategies) while completing two frustration eliciting tasks [attractive toy in a transparent box; Goldsmith, Reilly, Lemery, Longley, & Prescott, 1999, and unsolvable puzzles task; Smiley & Dweck, 1994].…”
Section: Methods Of Measurementmentioning
confidence: 99%
“…Individuals with ASD are known to react to emotionally aversive situations with behaviors that serve escape functions [Jahromi, Meek, & Ober-Reynolds, 2012], and inhibiting prosocial emotion-expressive behavior is also more common in individuals with ASD than in TD peers [Samson et al, 2012]. Individuals with ASD have been noted to have an overall higher rate of physiological arousal, making the regulation of emotional responses more difficult [Bal et al, 2010;Hirstein, Iversen, & Ramachandran, 2001;Kylliainen & Hietanen, 2006].…”
Section: Modal Model Of Ermentioning
confidence: 99%
“…Maladaptive or idiosyncratic strategies (see Laurent and Rubin 2004), such as avoidance, venting, or crying, are used more frequently by children with ASD (Konstantareas and Stewart 2006;Jahromi et al 2012). Recently, one study suggested that children and adolescents with ASD made less frequent and less effective use of adaptive emotion regulation strategies such as goal-directed behaviors or social support seeking compared to typically developing youth (Jahromi et al 2012). This decreased use of adaptive and increased use of maladaptive emotion regulation strategies has also been shown in adults, where individuals with ASD were found to use less cognitive reappraisal, but more often expressive suppression than matched non-ASD participants (Samson et al 2012).…”
Section: Introductionmentioning
confidence: 99%